Principles of heat transfer - Kreith, Frank (Brooks/Cole, 2000)
Frank Kreith and Mark Bohn's PRINCIPLES OF HEAT TRANSFER is known and respected as a classic in the field! The sixth edition has new homework problems, and the authors have added new Mathcad problems that show readers how to use computational software to solve heat transfer problems. This new edition features own web site that features real heat transfer problems from industry, as well as actual case studies.